Corporate Social Responsibility Effect on the Company Capitalization (the Results of an Empirical Study) - I. N. Tkachenko (Управленческие науки, 2016)
The aim of the study was to explore how Corporate Social Responsibility (CSR) affects on company capitalization through the lens of a stakeholder approach. The article presents the results of the empirical study of 12 largest Russian public companies in different sectors of economy with the most developed models of CSR. The data were sampled from the database compiled by the authors for the period of 2010- 2014. The relevant hypothesis was tested using the comparative analysis, the correlation-regressive model, and methods of value based management. The findings supported the prediction that fulfilling CSR has a significant impact on company capitalization. Informational portal of Moscow Interbank Currency Stock Exchange (MICSE) was used as companies’ capitalization data base source for defining series of analytical results. CSR data were received on the base of non-financial records which were posted on the companies’ official sites. The research methodology is based on theoretical developments and scientific instrumentarium involving the comparative analysis, economic and mathematic modeling and methods of value management. The necessity of using stakeholder approach giving the possibility to look at the problem of raising business efficiency via reaching companies’ social directivity in order to satisfy all the engaged sides is justified. The article formulates a number of hypotheses which were either proved or rejected in the process of research. With the help of the correlation-regressive model it was proved that not all the social investments into human capital development as one of the main aim of CSR events directly influence on companies efficiency and their capitalization, it was also found out that not all socially responsible investments in the development of human capital directly affect company’s sustainability. This conclusion can be used as a criterion for considering socially responsible investment policy and effective decision making. The findings of the study allowed the authors to lay down the guidelines for working out rational managerial decisions to foster company’s strategic efficacy.